A new species and new records of syringophilid mites (Acari: Prostigmata: Syringophilidae) from birds of Jordan - Głowska, Eliza; Skoracki, Maciej; Khourly, Fares (Zootaxa, 2007)
The first records of quill mites (Syringophilidae) from Jordan (Middle East) are presented. A new species, Picobia pycnonoti sp. nov. from the White-spectacled Bulbul Pycnonotus xanthopygos (Ehrenberg) (Passeriformes: Pycnonotidae) is described and illustrated. Additionally, eight bird species are reported as new hosts for syringophilid mites.